(untitled) (Research, Society and Development, 2020)
In the last decades, we have seen great changes in political, economic and social scenarios. These transformations have increasingly consolidated technological advances, directly affecting society through their use and, mainly, through the speed of information. This reflex can also be noticed in contemporary education, where there is a rush in the search for new educational practices in teaching. Thus, the project-based learning – PBL, even though it is a very old method, has been gaining more and more followers as an adequate proposition for the diverse educational needs of the current world. The objective of this research is to identify and analyze educational potentialities in contemporary times, as well as the challenges during the application of Project Based Learning in high school, through a systematic literary review. The qualitative research was about real situations in the daily life of basic education schools, outstandingly high school, where eleven researches were analyzed on some pedagogical experiences supported by active methodology, focusing on PBL. We identified positive aspects, as well as highlighted conflicting issues, since they can directly influence the application and success of the pedagogical project or even the development of students and teachers. Therefore, it is concluded that PBL can demonstrate a capacity for curricular, thematic and procedural articulation among students of basic education, promoting the development of the teaching and learning process, considered one of the most appropriate methodological initiatives to the demands observed in relation to training for the exercise of citizenship and training for the world of work, in line with current legislative assumptions and scientific, technological and cultural advances.